Cyanamide-inducible expression of homing nuclease I−SceI for selectable marker removal and promoter characterisation in Saccharomyces cerevisiae - Liam McDonnell; Samuel Evans; Zeyu Lu; Mitch Suchoronczak; Jonah Leighton; Eugene Ordeniza; Blake Ritchie; Nik Valado; Niamh Walsh; James Antoney; Chengqiang Wang; Carlos Horacio Luna-Flores; et al. (Synthetic and Systems Biotechnology)
In synthetic biology, microbial chassis including yeast Saccharomyces cerevisiae are iteratively engineered with increasing complexity and scale. Wet-lab genetic engineering tools are developed and optimised to facilitate strain construction but are often incompatible with each other due to shared regulatory elements, such as the galactose-inducible (GAL) promoter in S. cerevisiae. Here, we prototyped the cyanamide-induced I−SceI expression, which triggered double-strand DNA breaks (DSBs) for selectable marker removal. We further combined cyanamide-induced I−SceI-mediated DSB and maltose-induced MazF-mediated negative selection for plasmid-free in situ promoter substitution, which simplified the molecular cloning procedure for promoter characterisation. We then characterised three tetracycline-inducible promoters showing differential strength, a non-leaky β-estradiol-inducible promoter, cyanamide-inducible DDI2 promoter, bidirectional MAL32/MAL31 promoters, and five pairs of bidirectional GAL1/GAL10 promoters. Overall, alternative regulatory controls for genome engineering tools can be developed to facilitate genomic engineering for synthetic biology and metabolic engineering applications.